Superconductivity in heavily boron-doped silicon carbide - Kriener, Markus (Sci Technol Adv Mater, 2009)
The discoveries of superconductivity in heavily boron-doped diamond in 2004 and silicon in 2006 have renewed the interest in the superconducting state of semiconductors. Charge-carrier doping of wide-gap semiconductors leads to a metallic phase from which upon further doping superconductivity can emerge. Recently, we discovered superconductivity in a closely related system: heavily boron-doped silicon carbide. The sample used for that study consisted of cubic and hexagonal SiC phase fractions and hence this led to the question which of them participated in the superconductivity. Here we studied a hexagonal SiC sample, free from cubic SiC phase by means of x-ray diffraction, resistivity, and ac susceptibility.